Hadith #2582 - Jami' al-Tirmidhi - al-Rabi' bin Sbyh الربيع بن صبيح; Anas ibn Malik; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Waki' bin al-Jarrah وكيع بن الجراح (Jami' al-Tirmidhi)
“He will be given water of Sadid to drink, he will swallow it…” that the Prophet (s.a.w) said: ” It will be brought toward his mouth and he will dislike it, so whenever it is brought closer to him it will melt his face and the skin of his head will fall into it. Then whenever he drinks from it, his bowels will be severed until it comes out from his anus. Allah, the Blessed and Exalted says: “And they will be given water of Hamim to drink such that it cuts up their bowels…” and He s
Grade:

Hadith #3186 - Jami' al-Tirmidhi - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Rabi' bin Sbyh الربيع بن صبيح; Hammad bin Salama حماد بن سلمة; Waki' bin al-Jarrah وكيع بن الجراح (Jami' al-Tirmidhi)
“Al-Ash’ari said: ‘When (the following) was revealed: ‘And warn your tribe of near kindred (26:214)’ the Messenger of Allah (ﷺ) placed his fingers in his ears, raised his voice and said: ‘O Banu ‘Abd Manaf! Hearken!'”
Grade:

Hadith #2883 - Sunan Ibn Majah - al-Rabi' bin Sbyh الربيع بن صبيح; Anas ibn Malik; Da'ud bin al-Mhbr داود بن المحبر (Sunan Ibn Majah)
“When the ten days (of Dhul-Hijjah) begin, and one of you wants to offer a sacrifice, let him not remove anything from his hair or skin.”
Grade:

Hadith #3000 - Sunan Ibn Majah - al-Rabi' bin Sbyh الربيع بن صبيح; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Anas ibn Malik; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Let one of you eat with his right hand and drink with his right hand, and take with his right hand and give with his right hand, for Satan eats with his left hand, drinks with his left hand, gives with his left hand and takes with his left hand.”
Grade: